Institutions and foreign aid effectiveness in Sub-Saharan Africa - CEESAY, Adama (KDI School, 2021)
Many African countries heavily depend on foreign aid, however, the fact that most countries in the region record low income per capita despite receiving huge amounts of aid resources brings an obvious question about the validity of aid as a means to supporting economic growth and consequently eradicating extreme poverty in Africa. This study sought to examine the effect of six different dimensions of institutional/governance quality on aid effectiveness in Sub-Saharan Africa. The findings indicate that overall aid has a positive but small effect on economic growth in the sub-region. Furthermore, the effect of institutions on foreign aid effectiveness is positive above a threshold level of aid and negative below the threshold. Among the six dimensions of institutional quality examined ‘control of corruption’ has the most significant influence on aid effectiveness followed by ‘rule of law’ and ‘regulatory quality’. The main policy recommendation this paper provides is that increasing aid inflows to the region must be complemented by efforts to control corruption, advance rule of law, and improving regulatory quality for foreign aid to have a significant effect on economic growth.
Thesis(Master) -- KDI School: Master of Public Policy, 2021
Keywords: Economic assistance--Africa, Sub-Saharan